Parental support for free school lunches in Australian primary schools: associated factors and perceived barriers - Gozde Aydin; Claire Margerison; Anthony Worsley; Alison Booth (Cambridge University Press, 2023)
Abstract Objective: (1) To explore the feasibility of such programmes in Australia, this study examined parents' views on free school lunch provision. (2) To examine the associations between parents' demographic and personal characteristics and their support for free universal school lunches. Design: An online cross-sectional survey of parents. Setting: Australia, April 2021. Participants: Seven hundred and eighty-seven parents took the survey. They had a mean age of 40. The respondents were predominantly female (95 %) and had a university degree (72 %). Results: Fifty-three percentage of the respondents agreed that all students should have access to healthy and well-balanced, free school lunches. Parents were concerned about healthiness, catering, allergies and cost of school-provided school lunches. Ethnic background, universalism values and education levels were significantly associated with support for free school lunch provision. Non-native English-speaking parents were almost three times more likely to support free universal lunches in primary schools than their native English-speaking counterparts. Parents with higher universalism-concern values were more likely to endorse free lunches in primary school. However, the level of education was negatively associated with parents' support for free school lunches. Conclusions: The survey results highlight the complexity of parental views on free school lunch provision. Parents' concerns regarding lunches should be considered in developing school lunch programmes that meet the needs and preferences of diverse communities. These findings can be used to guide future primary school lunch provision initiatives.